Empathic and compassionate healthcare as a Christian spiritual practice - Pembroke, Neil (Practical theology, 2019)
It is argued that a Christian spirituality of healthcare provision is founded on agape. In the medical context, agape is expressed primarily through empathy and compassion. The love that a healthcare professional gives is manifested in two major modalities - namely, receptivity and extension. Empathy is an extension through the imagination into a patient's inner world of experience. It requires being receptive to the pain and distress that the patient displays and speaks about. The theological connection between empathic attunement and the Incarnation is developed. Compassion also involves feeling-with. This receptive stance is linked to rehem- or womb-compassion in the Hebrew Bible. Compassionate receptivity to the suffering of the patient drives a decision to extend oneself in order to alleviate it.